1989
DOI: 10.1093/infdis/159.5.860
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Towne Cytomegalovirus Vaccine Against Low-Passage Cytomegalovirus Administered as a Challenge

Abstract: To test the protective effect of Towne live attenuated human cytomegalovirus (HCMV) vaccine in normal individuals, we developed a parenteral challenge consisting of a low-passage isolate (Toledo stain) inoculated subcutaneously in graded doses. This challenge virus caused a mild mononucleosis syndrome in seronegative individuals at doses of 10 or 100 pfu. The illness was accompanied by atypical lymphocytosis, raised hepatic enzymes, excretion of HCMV and HCMV-specific immune responses. Naturally seropositive v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
110
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(112 citation statements)
references
References 23 publications
2
110
0
Order By: Relevance
“…The time of initial infection was estimated to be the midpoint between the last negative and the first positive assay. Previous studies of uninfected adult volunteers inoculated with an unattenuated CMV viral strain found that CMV viruria and CMV-specific Ab were detectable by ϳ5 and 6 wk after viral inoculation, respectively (14). Therefore, screening for CMV acquisition based on either culture-proven viruria or seropositivity for CMV Ab should result in a very similar estimate of the duration of infection.…”
Section: Screening For Primary CMV Acquisitionmentioning
confidence: 95%
“…The time of initial infection was estimated to be the midpoint between the last negative and the first positive assay. Previous studies of uninfected adult volunteers inoculated with an unattenuated CMV viral strain found that CMV viruria and CMV-specific Ab were detectable by ϳ5 and 6 wk after viral inoculation, respectively (14). Therefore, screening for CMV acquisition based on either culture-proven viruria or seropositivity for CMV Ab should result in a very similar estimate of the duration of infection.…”
Section: Screening For Primary CMV Acquisitionmentioning
confidence: 95%
“…While protective, this natural immunity is incomplete. [27][28][29] Recent studies in Brazil, where almost all congenital infections occur in infants born to CMV-experienced women, 30 are consistent with a significant worldwide burden of CMV congenital disease due to recurrent infections. 13,14 Recurrent infections are the result of reactivation of resident viruses as well as the acquisition of new virus strains (re-infection or super-infection).…”
mentioning
confidence: 73%
“…96 Inadequate efficacy of the Towne LACV in healthy women of childbearing age, 29 however, together with the demonstration that the Towne LACV had been over-attenuated by acquisition of large deletions 106 prompted interest in alternate LACVs. These have included attempts by Aviron (now MedImmune/AstraZeneca) to 'dial up' the Towne strain by swapping genome segments from a less-attenuated strain (Toledo, used as challenge virus in Towne-LACV studies 28 ), in an effort to add back genes that the LACV stocks had lost on passage. This 'dial-up' effort has progressed slowly over the past twenty years due to safety concerns raised by experts in the field during an FDA review in 1999.…”
Section: Live Attenuated Virus Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been shown that clinical isolates of HCMV carry at least 19 additional genes not found in laboratory strains (Cha et al, 1996). The deletion of these genes in the laboratory-adapted strains AD169 and Towne correlates with differences in replication and an attenuated phenotype after inoculation of human volunteers (Brown et al, 1995 ;Plotkin et al, 1989). A genotyping scheme for HCMV strains Author for correspondence : Thomas Stamminger. Fax j49 9131 8522101. e-mail tsstammi!viro.med.uni-erlangen.de stream of a β-globin reporter gene.…”
Section: Introductionmentioning
confidence: 99%